2013
DOI: 10.1177/1066480713505062
|View full text |Cite
|
Sign up to set email alerts
|

Creating Respect in Couples

Abstract: Respect is one of the cornerstones of healthy relationships. The article features the Couple's Respect Questionnaire as a tool for couples to explore specific examples and qualities of respect in their relationship. The four Rs are presented as core components of respect. They consist of Respect for differences, Responsibility (ability to respond respectfully), Review (a willingness to review), and Release (a willingness to release). Following a profile of the assessed behaviors, a stepwise procedure is outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Researchers have examined the influence of religiosity in strengthening marital satisfaction; however, there is a shortage of studies seeking to understand the influence of religiosity on marital satisfaction in the Pakistani context [1]. In several societies, marriage is regarded as a religious sacrament as married couples typically pledge to spend their lives together in the eyes of God and marriage has been intimately associated with religion [2]. Religion emphasizes marriage and couples who believe in religion make a stronger marital commitment, which strengthens their marital relationship [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have examined the influence of religiosity in strengthening marital satisfaction; however, there is a shortage of studies seeking to understand the influence of religiosity on marital satisfaction in the Pakistani context [1]. In several societies, marriage is regarded as a religious sacrament as married couples typically pledge to spend their lives together in the eyes of God and marriage has been intimately associated with religion [2]. Religion emphasizes marriage and couples who believe in religion make a stronger marital commitment, which strengthens their marital relationship [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Other works have demonstrated that interpersonal acceptance across close adult relationships (i.e., parent, best friend, romantic partner) is associated with positive outcomes (e.g., better mood and life satisfaction; Lac & Luk, 2019). Mutual respect for differences (e.g., age, culture, unique preferences) between partners has been proposed as an essential element of a healthy intimate relationship (Eckstein et al, 2014). Other works suggest that respect for autonomy (i.e., regard for autonomous action or decision making) prevents unhealthy patterns of codependency and destructive power and control dynamics in couple relationships (Osamor & Grady, 2018).…”
Section: Accumulating Evidence For the Importance Of Individuality In...mentioning
confidence: 99%
“…Given the potential importance of individuation in couple relationships, we aimed to develop an internally consistent, validated, and economical self-report questionnaire. Based on contemporary theorizing on individuality in couples (Bell, 2021; Lawrence et al, 2011; Brock & Lawrence, 2011) and closely related constructs (Cordova et al, 2014; Eckstein et al, 2014; Osamor & Grady, 2018), we conceptualized individuality as the extent to which someone feels respected for their individuality by their partner and experiences personal autonomy in the relationship . That is, each partner will perceive the degree to which they are free to be themselves in the context of the intimate relationship.…”
Section: Accumulating Evidence For the Importance Of Individuality In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mitt., and Physcomitrium sphaericum (C.F.Ludw. ex Schkuhr) Brid., belonging also to the family Funariaceae (Benkert 2007, Eckstein & Eckstein 2013 Benkert) have a different position in the tree (Fig. 1).…”
Section: Phylogenetic Analysismentioning
confidence: 99%